Effect of soil tillage on diversity and abundance of macrofungi associated with chestnut tree in the Northeast of Portugal - Baptista, Paula (2011)
European chestnut trees (Castanea sativa Mill.) are of great economic importance for wood and fruit production in the northeast of Portugal. In order to maintain the soil free of weeds, farmers traditionally practice several superficial tillages along the year. Phytosanitary problems mainly related with increasing Phytophtora cinnamomi contamination of soils are progressively changing these practices.